The Shadow Economy's Role in Indonesia's Digital Economic Structure - Apriyanto, Apriyanto (The Es Economics and Entrepreneurship, 2025)
The informal economy continues to play a vital role in Indonesia’s socioeconomic landscape, providing livelihoods for millions who remain outside the formal sector. With the rapid expansion of digital technologies, informal workers and entrepreneurs are increasingly adopting digital tools to sustain and expand their economic activities. This study examines the role of the informal economy in Indonesia’s digital economy using a qualitative approach. Data were gathered through in-depth interviews with five informants actively engaged in informal sectors, including online retail, food services, digital freelancing, and street vending. The findings reveal that digital platforms enhance market access, promote financial inclusion, and improve livelihood resilience for informal actors. However, challenges remain, such as limited digital literacy, unstable infrastructure, and unclear regulatory frameworks. These factors hinder the ability of informal workers to fully integrate into the digital economy. The study concludes that inclusive policies, digital literacy programs, and infrastructure support are essential to maximize the contributions of the informal economy to Indonesia’s digital transformation.